(untitled) (Chittagong University Journal of Biological Sciences, 2024)
In response to the scarcity of grade-specific academic self-efficacy scale, the present study was aimed to adapt a scale for measuring academic self-efficacy for higher secondary students in the context of Bangladesh. Main objective of this study was to assess psychometric properties of the Academic Self-efficacy Scale for Bangladeshi higher secondary students. This measure was administered on a sample 207 higher secondary students who were selected from 3 administrative districts of Bangladesh by non-probability sampling techniques. Psychometric properties were assessed through item analysis (item-total correlation, Cronbach’s Alpha and split-half reliabilities), differential item function, and Pearson product moment correlation coefficient (Predictive validity). One item excluded from the scale as this item had insufficient item-total correlation. Findings revealed that this scale had sufficient internal consistency reliabilities and predictive validity and suggested that this could be applicable for assessing academic self-efficacy of higher secondary students in Bangladesh. The Chittagong Univ. J. B. Sci.,Vol. 10(1 and2):149-156, 2020